2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of S100A8 in mice brain after focal cerebral ischemia reperfusion

Abstract: BACKGROUND:Recent studies have showed that S100A8 has been implicated in the pathobiology of inflammatory disorders, and that cerebral ischemia reperfusion (I/R) rapidly activates inflammation responses via Toll-like receptor 4 (TLR4). This study aimed to explore the expression of S100A8 and the relationship between S100A8 and TLR4 in focal cerebral ischemia reperfusion injury.METHODS:C3H/HeJ mice (n=30) and C3H/HeN mice (n=30) were divided randomly into a C3H/HeJ model group (n=18), a C3H/HeJ control group (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…These lines of evidence imply that calprotectin might play a pivotal role in the pathogenesis of cardiovascular diseases. Although previous animal studies have demonstrated that calprotectin could promote neuroinflammation and exacerbate the pathology of AIS ( 20 ), limited evidence is available in human studies, with only two studies investigated the association between calprotectin and prognosis of stroke ( 21 , 22 ). Specifically, Guo et al investigated the association between baseline calprotectin levels and 3-month functional outcomes of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…These lines of evidence imply that calprotectin might play a pivotal role in the pathogenesis of cardiovascular diseases. Although previous animal studies have demonstrated that calprotectin could promote neuroinflammation and exacerbate the pathology of AIS ( 20 ), limited evidence is available in human studies, with only two studies investigated the association between calprotectin and prognosis of stroke ( 21 , 22 ). Specifically, Guo et al investigated the association between baseline calprotectin levels and 3-month functional outcomes of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the importance of S100a8 in the pathobiology of inflammatory disorders ( 11 , 37 , 38 ). Treatment with S100a8/a9 has been demonstrated to markedly increase the secretion of the aforementioned pro-inflammatory cytokines in cultured BV2 microglial cells ( 14 ). Notably, S100A8 induces cytokine expression via the ROS-dependent activation of NF-κB ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that S100a8 is involved in the pathobiology of inflammatory disorders ( 13 ). S100a8 is highly expressed in the brains of mice following focal cerebral I/R injury ( 14 ). Increasing evidence suggests that S100a8/a9 genes are significantly upregulated during the early stages of myocardial I/R injury ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic outcomes were graded as: 0, normal; 1, forepaw monoparesis; 2, circling to right; 3, falling to right; and 4, no spontaneous walking and depressed consciousness (45). The brain was cut into 2 mm thick coronal blocks and stained in the dark with 2, 3, 5‐triphenyltetrazolium chloride for 1 h at 37°C, and the infarct volume was calculated (46). Where indicated, 1 μg/kg (18 nmol/kg) sTM or an equimolar dose of scFv/TM was injected into the right jugular vein 20 min before MCA occlusion.…”
Section: Methodsmentioning
confidence: 99%